DIY satellite platforms - Antunes, Sandy (Sebastopol, California O'Reilly Media Inc., 2012)
Can any hobbyist build a satellite? Our DIY guide steps you through designing and building a base picosatellite platform tough enough to withstand launch and survive in orbit. If you have basic maker skills, you can build a space-ready solar-powered computer-controlled assembly suitable for attaching instruments and rocketing into space.
Subtitle on cover: Building a space-ready general base picosatellite for any mission.
"Project book ; Space-ready systems ; building a space-ready general base picosatellite for any mission"--Cover.
Keywords: Microspacecraft -- Design and construction; Artificial satellites -- Design and construction